2017
DOI: 10.1055/s-0043-120570
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Progression Rate of Diabetic Retinopathy in Type 2 Diabetes Patients in Correlation with the Duration of Diabetes

Abstract: Within the first 10 years of diabetes duration, the prevalence of retinopathy is low and the progression infrequent. Most patients have a non-proliferative form which can be reversible and rarely requires interventions. Patients with DM2 without retinopathy and good glycaemic control do not run into additional risk from expanding funduscopy intervals to biennial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
45
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 31 publications
8
45
2
4
Order By: Relevance
“…Therefore, the prevalence of DR in patients would rise substantially when the patient's diabetic durations were over 10 years. 27 Some studies also found that the longer duration of diabetes, the higher chance of retinopathy appeared; with impact on the risk of DR. 17,24,28 The result of those studies were corresponding to our study. Therefore, well controlled earlier could prevent and delay the progression of DR in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the prevalence of DR in patients would rise substantially when the patient's diabetic durations were over 10 years. 27 Some studies also found that the longer duration of diabetes, the higher chance of retinopathy appeared; with impact on the risk of DR. 17,24,28 The result of those studies were corresponding to our study. Therefore, well controlled earlier could prevent and delay the progression of DR in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported a high prevalence (ranging from 11.9-43.1 %) of DR in adults with T2DM mainland China [20,21]. Some studies in Denmark and Germany showed that the prevalence of DR were 21.2 and 25.8 % in patients with T2DM [22,23]. The prevalence of DR patients was 7.2 and 13.1 % , in which young patients newly diagnosed with T2DM aged ≤ 21 years were enrolled in a large US managed-care network and a new diagnosis of T2DM in China, respectively [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that increased duration of diabetes, poor blood glucose control, ineffective blood pressure control, and genetic factors are the major risk factors for DR [23,29,30]. In our study, FC-P and FBG were positively correlated with DR in the patients newly diagnosed with T2DM (P < 0.05), and the OR values of FC-P and FBG were 7.685 and 1.256, which indicate that FC-P levels were the highest risk factors for DR followed by FBG.…”
Section: Discussionmentioning
confidence: 99%
“…DR has a delayed onset and a slow, gradual progression over many years and can even regress when the disease is in an early mild form. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%